Lenalidomide before and after Autologous Hematopoietic Stem Cell Transplantation in Multiple Myeloma - S. A. Tuchman; N. J. Chao; C. G. Gasparetto (Advances in Hematology)
Although multiple myeloma remains incurable outside of allogeneic hematopoietic stem cell transplantation, novel agents made available only in the last few decades have nonetheless tremendously improved the landscape of myeloma treatment. Lenalidomide, of the immunomodulatory class of drugs, is one of those novel agents. In the non-transplant and relapsed/refractory settings, lenalidomide clearly benefits patients in terms of virtually all meaningful outcomes including overall survival. Data supporting the usage of lenalidomide as part of treatment approaches incorporating high-dose chemotherapy with autologous stem cell support (ASCT) are less mature as pertains to such long-term outcomes and toxicity, and lenalidomide is not currently approved by regulatory agencies for use in the context of ASCT in either the United States or Europe. That said, relatively preliminary efficacy data describing lenalidomide as a component of ASCT-based treatment approaches to MM are indeed promising, and consequently lenalidomide’s role in ASCT-based treatment strategies is growing. In this review we summarize existing data that pertains to lenalidomide in the specific context of ASCT, and we share our thoughts on how our own group applies these data to approach this complex issue clinically.